PELAKSANAAN PEMBINAAN YANG BERSIFAT KEMANDIRIAN TERHADAP NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS II B SLAWI - Maryanto Maryanto; Diah Rahmawati; Indrati Rini (Jurnal Pembaharuan Hukum, 2014)
The concept of stewardship at the empirical level has been carried out by the Penitentiary Class II B Slawi, such as guidance that is independence, among others, by providing skills training to inmates with the limitations and shortcomings that exist in the Penitentiary Class II B Slawi. Some of the constraints faced by the Penitentiary Class II B Slawi include: coaching program has not run continuously, the lack of awareness of prisoners following the activities, limitation of infrastructure, limited skills program instructor and the persistence of the public rejection of the former inmates despite having sufficient skills. The efforts that have been and are being carried out include: create a continuous program implementation and sanctions, build cooperation, give positive information about inmates, staff training and support program proposals.